Communications strategies by advocacy groups, law enforcement, and journalists about sex trafficking: impacts of agenda building, agenda setting, and framing - Burnham, Annie, author; Switzer, Jamie, advisor; Hallahan, Kirk, committee member; Kelly, Kathleen, committee member (Colorado State University. Libraries, 2014)
This study is based on 15 qualitative in-depth interviews with 15 communications professionals in Denver, Atlanta and Raleigh, and represents advocacy groups, law enforcement and journalists to better understand communications messaging about sex trafficking. This study examines the ways the three aforementioned groups develop communication messages about sex trafficking using agenda building, agenda setting, and framing. Sex trafficking is defined as the sexual exploitation of an individual for profit, a subset of human trafficking. Economic factors, public policy factors, and sociocultural factors are highlighted from the data to determine what influences play into message creation. Results show that advocacy groups, law enforcement, and journalists all engage in some level of agenda building, agenda setting, and framing. The results show that all three groups participated most in framing the issues, whether through an awareness frame, a crime frame, or a community issue frame. Additionally, sociocultural factors played the largest role in influencing message creation.
Keywords: agenda building; agenda setting; Atlanta; Denver; framing; sex trafficking